MOS6 and TN13 in plant immunity - Lüdke, Daniel (Plant Signal Behav, 2018)
The Arabidopsis nuclear transport receptor IMPORTIN-α3/MOS6 (MODIFIER OF SNC1, 6) is required for constitutive defense responses of the auto-immune mutant snc1 (suppressor of npr1-1, constitutive 1) and contributes to basal disease resistance, suggesting a role in nuclear import of defense-regulatory cargo proteins. We recently showed that MOS6 selectively interacts with TN13, a TIR-NBS protein involved in basal resistance to Pseudomonas syringae pv. tomato (Pst) DC3000 lacking the effectors AvrPto and AvrPtoB. Consistent with a predicted N-terminal transmembrane domain, TN13 localizes to the endoplasmic reticulum (ER) and the nuclear envelope (NE) where it interacts with MOS6 in a transient expression assay. Here, we propose a model that summarizes the subcellular localization, association and function of TN13 and MOS6 in plant defense signaling.